Battlefield memories: the legacy of Bilbao’s Iron Belt (Spanish Civil War) through digital humanities - Tania González-Cantera; Xavier Rubio-Campillo (Humanities & Social Sciences Communications)
Abstract The memorialisation of conflict heritage is a complex process due to its traumatic origin. One iconic example is the Iron Belt, a mythical line of fortifications defending Bilbao during the Spanish Civil War, which has been repurposed as a political tool to convey diverse interpretations of the conflict. This article explores the dynamics of its memorialisation and examines how the same archaeological record can generate contrasting war narratives. To address these challenges, the study employs an innovative digital humanities framework to document, analyse, and interpret four sections of the Iron Belt in which archaeological structures remain preserved. The framework establishes a geospatial database model, analysed using Geographic Information Systems and data visualisation techniques. This methodology facilitates the cross-referencing of interconnected heritage variables –such as conservation, dissemination activities, and the institutions responsible for them–, that have not previously been quantitatively assessed. Results indicate divergent heritage management approaches, shaped by different political, economic, and social contexts at the local level. This suggests that the pastness of the Iron Belt is actively constructed in the present through “past presencing” policies. Additionally, the study highlights the critical role of local entities and associations, which often act as key agents in initiating the memorialisation of complex heritage.